Using a proteometabolomic approach to investigate the role of Dufour's gland in pheromone biosynthesis in the social wasp Polybia paulista - Esteves, Franciele Grego [UNESP]; Santos-Pinto, José Roberto Aparecido dos [UNESP]; Saidemberg, Daniel Menezes [UNESP]; Palma, Mario Sergio [UNESP] (Elsevier, 2017)
Dufour's gland is associated with the venom apparatuses of social wasps and bees. This location and its evolutionary adaptations indicate that it could be involved in the production of alarm pheromones in the social wasp Polybia paulista. To investigate this hypothesis, the volatile composition of this gland was analyzed and compared to that in the venom. Eighteen compounds were identified as secreted by Dufour's gland, and 16 of these compounds were also identified in the venom, suggesting that the compounds produced by the gland are secreted and mixed with venom in the venom reservoir of this wasp. These compounds were subjected to a field bioassay to investigate their potential action as alarm pheromones. Alcohols and aldehydes elicited the alert behavior in workers, luring them outside the nest, whereas acids attracted the workers in the direction of the source; fatty acid methyl esters elicited aggression. These results suggest that Dufour's gland produces alarm pheromones. To corroborate this hypothesis the proteomic complement of this gland was assigned using a shot-gun strategy; 59 proteins were identified, and the results indicate specialization of Dufour's gland for the metabolism of fatty acids (elongation, esterification unsaturation, reduction, and decarboxylation) in the biosynthesis of alarm pheromones. Biological significance The present knowledge about the role of Dufour's gland among aculeate Hymenoptera insects suggests that it may have many different roles related to the biosynthesis and secretion of chemical markers for different biological functions, though none are related to the elicitation of alarm behaviors for coordinating a mass attack of the colony against intruders. The present study combined the analysis of secreted volatile compounds (as metabolites) with proteome assignments and a field bioassay with synthetic compounds to clearly demonstrate that Dufour's gland does in fact biosynthesize alarm pheromones in social wasps. This strategy may be reproduced in other investigations related to pheromone production in other insects.
Keywords: Chemical communication; GC–MS; Mass spectrometry; Metabolomics; Pheromone; Shotgun proteomics